2023
DOI: 10.1055/a-1987-3682
|View full text |Cite
|
Sign up to set email alerts
|

Immune Plasma for the Treatment of COVID-19: Lessons Learned so far

Abstract: COVID-19 convalescent plasma (CCP) has been explored as one of the treatment options for COVID-19. Results of many cohort studies and clinical trials have been recently published. At first glance, the results of the CCP studies appear to be inconsistent. However, it became clear that CCP is not beneficial if CCP with low anti-SARS-CoV-2 antibody concentrations is used, if it is administered late in advanced disease stages, and to patients who already mounted an antibody response against SARS-CoV-2 at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…Among the immunomodulatory agents, passive antibody therapies including neutralizing monoclonal antibodies (mAbs), hyperimmunoglobulin and convalescent plasma (CP) have been early and successfully used [3]. In comparison with monocloncal antibodies, immune plasma from individuals immunized by both a natural SARS-CoV-2 infection and SARS-CoV-2 vaccination retained neutralizing activity against new variants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the immunomodulatory agents, passive antibody therapies including neutralizing monoclonal antibodies (mAbs), hyperimmunoglobulin and convalescent plasma (CP) have been early and successfully used [3]. In comparison with monocloncal antibodies, immune plasma from individuals immunized by both a natural SARS-CoV-2 infection and SARS-CoV-2 vaccination retained neutralizing activity against new variants [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the administration of high titer CCP in early stages of disease to outpatients significantly reduced disease progression and hospitalization rate [9] . Despite the development of therapeutic antibodies, CCP may be in case of newly emerging SARS-CoV-2 variants also an important future treatment option [10] , [11] . Since CCP-donors are like first-time donors with an elevated risk for window-period transmission of blood borne viruses, pathogen reduction treatment (PRT) may be a way mitigating such risk.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 remains a highly relevant topic, on which Schrezenmeier 3 et al provides an overview of the use of immune plasma to describe both the benefits of immune plasma in general and the use of reconvalescent plasma in COVID-19 in particular. His plenary lecture on convalescent plasma presents the studies on this topic.…”
mentioning
confidence: 99%